A Comparative Study of Parenting Practices and Juvenile Delinquency between China and the United States. Issue 4 (3rd April 2023) - Li, Spencer D.; Liu, Tzu-Hsuan; Xia, Yiwei
ABSTRACT: This study examines the differences in parenting practices and their effects on juvenile delinquency between China and the United States. Its principal goal is to gain a more culturally relevant understanding of the possible ways of preventing delinquency through the improvement of parenting styles. The analyses were based on a nationally representative sample of American adolescents and a probability sample of Chinese adolescents in the same age group. To increase data comparability, the study employed similar measures of parenting practices and delinquency in the two samples. The analysis indicated that the American adolescents perceived a higher level of parental responsiveness but a lower level of parental control than did the Chinese adolescents. While parental responsiveness was inversely related to delinquency in both samples, parental control predicted lower delinquency only in the U.S. sample. Moreover, the negative relationship between parental monitoring and delinquency was stronger among the American adolescents than among the Chinese adolescents. The results underscore the need to consider cultural differences when assessing the impact of parenting practices on delinquency, or when applying the research findings to delinquency prevention programs.